2007 International Conference on Electromagnetics in Advanced Applications 2007
DOI: 10.1109/iceaa.2007.4387311
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Properties of the Discontinuous Galerkin Method for Maxwell Equations

Abstract: We investigate the conservation properties of the centered DG formulation for Maxwell equations. In particular, we state the problem and derive the criteria for charge conservation. It is shown that the centered scheme guarantees strict charge conservation for Cartesian discretizations with tensor product basis functions of arbitrary order. On unstructured grids, however, the conservation of charge is inherently violated. The reasons for this are of purely topological nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Thus, spurious numerical solutions exist which are not compatible with (4). This statement is, in fact, part of a general result obtained by Gjonaj et al [2007] showing that any DG-FEM will violate charge conservation independently from the type of the approximation spaces used in the formulation.…”
Section: Dg-femmentioning
confidence: 63%
See 1 more Smart Citation
“…Thus, spurious numerical solutions exist which are not compatible with (4). This statement is, in fact, part of a general result obtained by Gjonaj et al [2007] showing that any DG-FEM will violate charge conservation independently from the type of the approximation spaces used in the formulation.…”
Section: Dg-femmentioning
confidence: 63%
“…A major issue related with DG-FEM, however, is the unphysical charge distribution induced by discretization which gives rise to spurious numerical solutions. In the work by Gjonaj et al [2007] it was shown on topological grounds that, except for tensor product formulations on Cartesian grids, any other DG-FEM will violate charge conservation independently from the type of the approximation spaces used. The appearance of unphysical solutions related to the violation of charge conservation has consequences on both the numerical accuracy and on the stability of time domain simulations.…”
Section: Introductionmentioning
confidence: 99%
“…There exists a large amount of literature on algorithms for solving this problem, coming as well from the mathematics as from the physics community, and a recent survey is available in [19]. However, despite some insightful studies on the proper discrete Gauss laws that should be preserved by a DG-PIC scheme [36,48], we believe that the problem of designing a stable charge-conserving coupling for non-conforming solvers remained an open one. In this context the non-conforming methods obtained with our structure-preserving approach may be seen as general and satisfactory solution.…”
Section: Compatible Maxwell Solvers With Particles Imentioning
confidence: 99%
“…However, DG formulations exhibit spurious mode solutions due to violation of charge (and possibly energy) conservation [6].…”
Section: Introductionmentioning
confidence: 99%